A diamino-substituted carbodiphosphorane as strong C-donor and weak N-donor: isolation of monomeric trigonal-planar L·ZnCl2. Issue 58 (15th June 2020) - Kroll, Alexander; Steinert, Henning; Scharf, Lennart T.; Scherpf, Thorsten; Mallick, Bert; Gessner, Viktoria H.
Abstract : Studies of the reactivity and coordination properties of the diamino-carbodiphosphorane 1 revealed that 1 is a weak N donor, but strongly coordinates via the carbon atom thus allowing the isolation of low-valent metal species. Abstract : The isolation, structural characterization and coordination chemistry of a di(amino)-substituted carbodiphosphorane (CDP) are reported. Compared to the analogue, dianionic bis(iminophosphoryl)methandiides, the CDP is a stronger C-, but much weaker N-donor which led to the isolation of solely C-coordinated metal complexes amongst an unusual monomeric trigonal-planar L·ZnCl2 complex.